Protective Effect of Phosphates and Fluoride on the Dissolution of Hydroxyapatite and Their Interactions with Saliva - Manarelli, Michele M. [UNESP]; Pessan, Juliano P. [UNESP]; Delbem, Alberto C.B. [UNESP]; Amaral, Jackeline G. [UNESP]; Paiva, Mayra F. [UNESP]; Barbour, Michele E. (Karger Publishers, 2017)
This study aimed to investigate the effect of phosphates and fluoride, alone or in combination, and the influence of salivary pellicle on hydroxyapatite (HA) dissolution. The baseline dissolution rate of HA discs was measured using a pH-stat system (0.3% citric acid, pH 3.2). In the first series of experiments, HA discs (n = 8/group) were treated with: a placebo solution (PLA, deionised water); sodium trimetaphosphate (TMP), sodium tripolyphosphate (TRI) and sodium pyrophosphate (PYRO) at 1 or 8%; 500 ppm F; 1,100 ppm F; 1,100 ppm F/1% TMP; 1,100 ppm F/8% TMP; 1,100 ppm F/1% TRI; 1,100 ppm F/8% TRI. In the second phase, HA discs were immersed in pooled human saliva (37°C/2 h) and treated with PLA, 1,100 ppm F/1% TMP, 1,100 ppm F/8% TMP, 1,100 ppm F/1% TRI, and 1,100 ppm F/8% TRI. After treatments, final dissolution rates were measured from 3 consecutive 30-min assays. Statistical analyses were performed using 2-way ANOVA followed by the Fisher test (α = 0.05). The type and concentration of phosphate tested significantly influenced HA dissolution; 8% TRI showed the highest reduction (36.9%) among all treatment solutions. Fluoride alone (1,100 ppm F) significantly reduced HA dissolution by 20.7%. When fluoride and phosphates were associated, 1,100 ppm F/1% TMP, 1,100 ppm F/8% TMP, and 1,100 ppm F/8% TRI showed the highest percentage reductions of dissolution (40.3-46.1%). Salivary pellicle led to a greater and more sustained protective effect of the treatment solutions compared to their counterparts without salivary coating. It was concluded that the association of phosphate and fluoride enhanced their protective effect against HA dissolution when compared with these compounds alone, especially in the presence of salivary pellicle.
Keywords: Fluoride; Hydroxyapatite; Pellicle; Polyphosphates; Saliva